Mikrophonie I/Micorphony I: Colour film by Sylvain Dhomme 1966 - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2007)
Studio recording of MICROPHONY I with the Stockhausen - Ensemble. Short introduction byStockhausen in French and German ( English transcription available )